Kinetic analysis of mechanoradical formation during the mechanolysis of dextran and glycogen - Doi, Naoki; Sasai, Yasushi; Yamauchi, Yukinori; Adachi, Tetsuo; Kuzuya, Masayuki; Kondo, Shin-ichi (Beilstein Journal of Organic Chemistry, 2017)
A detailed electron spin resonance (ESR) analysis of mechanically induced free radicals (mechanoradicals) formation of glucose-based polysaccharides, dextran (Dx) and glycogen (Gly) was performed in comparison with amylose mechanoradicals. The ESR spectra of the samples mechanically fractured at room temperature were multicomponent. The radical concentration of Dx and Gly mechanoradicals gradually decreased during vibratory milling after reaching the maximum value. Although the molecular weight of Dx or the particle diameter of Gly steeply diminished until reaching the each maximum value of radical concentration, after that the molecular weight or the particle diameter slowly decreased. These results suggested that Dx and Gly mechanoradicals might be more unstable than amylose radicals possessing an intramolecular helical structure due to the branched structure.
Keywords: dextran; electron spin resonance (ESR); glycogen; mechanoradical; polysaccharide